Baroreflex activation therapy in patients with prior renal denervation. Issue 8 (August 2016) - Wallbach, Manuel; Halbach, Marcel; Reuter, Hannes; Passauer, Jens; Lüders, Stephan; Böhning, Enrico; Zenker, Dieter; Müller, Gerhard A.; Wachter, Rolf; Koziolek, Michael J.
Abstract : Background: Both baroreflex activation therapy (BAT) and renal denervation modulate sympathetic activity. The aim of this study was to systematically investigate whether additive modulation of autonomic nervous system by BAT lowers blood pressure (BP) in patients who still suffer from uncontrolled resistant hypertension despite prior renal denervation. Methods: From 2012 to January 2015, patients treated with BAT for uncontrolled resistant hypertension, who prior received renal denervation were consecutively analyzed in four German centers for hypertension. Analyses of office BP, 24-h ambulatory BP, central hemodynamics, parameters of renal function were performed. Results: A total of 28 patients, who underwent renal denervation at least 5 months before and still suffer from uncontrolled BP, were subsequently treated with BAT. The office SBP decreased from 182 ± 28 to 163 ± 27 mmHg ( P  < 0.01) with a responder rate of 68% (office SBP reduction ≥10 mmHg) at month 6, whereas the number of prescribed antihypertensive drug classes remained unchanged (6.2 ± 1.5 vs. 6.0 ± 1.7, P  = 0.30). Serum creatinine, estimated glomerular filtration rate and cystatin C remained stable ( P  = 1.00, P  = 0.41 and P  = 0.22, respectively), whereas albuminuria was significantly reduced by a median of −29% ( P  = 0.02). Central SBP (−15 ± 24 mmHg, P  = 0.047) and end systolic pressure (−14 ± 20 mmHg, P  = 0.03) were significantly reduced. Conclusion: The present data demonstrate that BAT may exert BP-lowering as well as antiproteinuric effects in patients with prior renal denervation. However, precise evaluation of BAT effects in patients with prior renal denervation will need randomized controlled trials using sham procedures.